Further Validation of the Norwegian Self-Efficacy for Therapeutic Mode Use - Victoria C. Ritter; Mikkel M. Thørrisen; Farzaneh Yazdani; Tore Bonsaksen (Occupational Therapy International)
Background. The Intentional Relationship Model (IRM) proposes six therapeutic modes as ways of relating to clients. The Norwegian self-efficacy for therapeutic mode use (N-SETMU) was found to have a one-component structure. However, its items reflect abstract concepts rather than concrete behaviors. Aim. To validate further the N-SETMU by linking its items to the Norwegian client assessment of modes (N-CAM), with 30 items constituting six scales (linked to each mode), possessing concrete, behavioral content. Methods. Occupational therapy students (n=111) completed the N-SETMU and the N-CAM derived items, along with sociodemographic information. Component structure was analyzed with Principal Components Analysis (PCA), internal consistency of scales with Cronbach’s α, and associations between scale scores with Pearson’s r. Results. All items on all N-CAM derived scales loaded on one latent component, except one item related to problem-solving. After removing this item, the scale functioned appropriately. Cronbach’s α for all N-CAM derived scales ranged 0.88–0.94, and the associations between the N-CAM derived scales and the corresponding N-SETMU items ranged between 0.60 (advocating) and 0.79 (encouraging). Conclusions. In view of the strong associations between the concrete, N-CAM derived scales and the abstract N-SETMU items, this study supports the concurrent validity of the N-SETMU.